Performance analysis of machine learning algorithms for Malware classification - Bushra, Raisa Hasan; Alam, Md Taukir; Saha, Aniruddho; Fahim, Nazmus Sakib; Binty, Nabila Mourium (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2022.